2021
DOI: 10.1016/j.isci.2021.102398
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-accelerated prediction of overpotential of oxygen evolution reaction of single-atom catalysts

Abstract: Summary The oxygen evolution reaction (OER) is a critical reaction for energy-related applications, yet suffers from its slow kinetics and large overpotential. It is desirable to develop effective OER electrocatalysts, such as single-atom catalysts (SACs). Here, we demonstrate machine learning (ML)-accelerated prediction of OER overpotential of all transition metals. Based on density functional theory (DFT) calculations of 15 species of SACs, we design a topological information-based ML model to map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…A Tafel slope value of 31 mV dec –1 for stretch-annealed catalysts thus suggests n b = 3 and ν = 2, which translated into the fact that the second (deprotonation of OH ad to form O ad ) and fourth (deprotonation of OOH ad to form OO ad ) electron transfer reactions can be the sluggish (energetically unfavorable) process ( ν = 2), and the fourth reaction acts as a major rate-determining step ( n b = 3). The proposed rate-determining step agrees with the proposed OER energetics on Cu, 73 , 74 further validating our Tafel analysis. The Tafel slope value varies between 31 and 84 depending on the pre-treatment of the PVdF-HFP substrate, probably due to the change in the OER energetics and/or the existence of the mixed rate-determining step.…”
Section: Results and Discussionsupporting
confidence: 85%
“…A Tafel slope value of 31 mV dec –1 for stretch-annealed catalysts thus suggests n b = 3 and ν = 2, which translated into the fact that the second (deprotonation of OH ad to form O ad ) and fourth (deprotonation of OOH ad to form OO ad ) electron transfer reactions can be the sluggish (energetically unfavorable) process ( ν = 2), and the fourth reaction acts as a major rate-determining step ( n b = 3). The proposed rate-determining step agrees with the proposed OER energetics on Cu, 73 , 74 further validating our Tafel analysis. The Tafel slope value varies between 31 and 84 depending on the pre-treatment of the PVdF-HFP substrate, probably due to the change in the OER energetics and/or the existence of the mixed rate-determining step.…”
Section: Results and Discussionsupporting
confidence: 85%
“…The ML method is commonly used in accelerating the prediction of the overpotential of oxygen evolution reactions. 27 , 28 DFT calculations showed that Fe–N 3 O-1, Fe–N 4 , Co–N 2 O 2 , Ni–N 2 O 2 , Ni–N 3 O-1, Ni–N 2 O 2 -1, and Fe–N 2 O 2 possessed higher OER performances than other units, and ML analysis indicated that the electrical properties of the active center were the most critical factor for catalytic OER performance. Subsequently, we synthesized one of the best performed Ni–N 2 O 2 coordination unit COFs.…”
Section: Introductionmentioning
confidence: 98%
“…The ML method is commonly used in accelerating the prediction of the overpotential of oxygen evolution reactions. 27,28 DFT calculations showed that Fe−…”
Section: ■ Introductionmentioning
confidence: 99%
“…[25] Topological information-based ML algorithms not only eliminate the need for data preprocessing (e.g., sorting and formatting) but also allow for a precise description of complex data features (e.g., symmetry and topological structures). [26] These unique advantages have led to surging interests in applying this ML algorithm in various domains, such as social networks, [27] drug discovery, [28] materials science, [29,30] and structural biochemistry [31] (e.g., AlphaFold [32] ). It is expected that such ML algorithms can be applied to the rational design of a wide range of atomic catalysts.…”
Section: Introductionmentioning
confidence: 99%